1990
DOI: 10.1084/jem.171.1.339
|View full text |Cite
|
Sign up to set email alerts
|

A mycobacterial 65-kD heat shock protein induces antigen-specific suppression of adjuvant arthritis, but is not itself arthritogenic.

Abstract: A nonapeptide epitope contained in the 65-kD species of heat shock protein of many mycobacterial species shares homology with a peptide on a mammalian cartilage link protein (1), with four of the amino acids identical. Structures containing this epitope, including proteoglycans extracted from human rheumatoid synovial effusions (2), induce proliferation ofan arthritogenic, rat T lymphocyte line (3) that has been subdivided into two clones, A2b and A2c, which, respectively, induce adjuvant arthritis or suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(79 citation statements)
references
References 12 publications
2
77
0
Order By: Relevance
“…The antigen that induces the immune response has been shown to be Hsp65, with the responsible epitope being peptide 180-186 (29). However, other components in CFA are important as well, because injection of only Hsp65 cannot trigger arthritis (30). Of note, the injection of mineral oil only can result in oil-induced arthritis; however, only a transient arthritis develops, in contrast to the chronic erosive arthritis seen in AIA (20,31).…”
Section: Evaluation Of Therapeutic Targets In Animal Models Of Arthritismentioning
confidence: 99%
“…The antigen that induces the immune response has been shown to be Hsp65, with the responsible epitope being peptide 180-186 (29). However, other components in CFA are important as well, because injection of only Hsp65 cannot trigger arthritis (30). Of note, the injection of mineral oil only can result in oil-induced arthritis; however, only a transient arthritis develops, in contrast to the chronic erosive arthritis seen in AIA (20,31).…”
Section: Evaluation Of Therapeutic Targets In Animal Models Of Arthritismentioning
confidence: 99%
“…However, most data collected to date do not support such antigenic mimicry to be a major trigger to autoimmune disease. In contrast, immunization with (mycobacterial) hsp60 has been found to protect animals from the development of arthritis in virtually all forms of experimental arthritis (7)(8)(9). Most evidence on the mechanism of the protective role of mycobacterial hsp60 has been obtained in adjuvant arthritis (AA) (10,11).…”
mentioning
confidence: 99%
“…During the 35-day pretreatment period none of the rats showed any clinical symptoms of A A, indicating that SNP is not arthritogenic (Billingham et al, 1990;Yang et al, 1990). In two separate experiments, we found after induction of A A that 11 out of 16 rats were completely protected (Table 1); furthermore on radiographs no indication of arthritis was found in these rats (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that the dominant immunogenic epitopes of some T cell-mediated experimental autoimmune diseases can be precisely defined by using disease inducing T cell clones as tools (Zamvile;a/,, 1986;van Eden e^o/,, 1988), In adjuvant arthritis (AA), a model of autoimmune arthritis inducible in certain strains of rats such as in Lewis rats, by heatkilled Mycobacterium tuberculosis (Pearson, 1956;1964;Taurog, Argentieri & McReynolds, 1988), a 65-kD mycobacterial heat-shock protein (HSP) has been proposed to be involved in the pathogenesis of AA (van Eden et al, 1988), Administration of the 65-kD HSP led to protection against AA and streptococcal cell-wall-induced arthritis in Lewis rats (van Eden et al, 1988;van den Broek et al, 1989;Billingham et al, 1990). A nonapeptide (Thr-Phe-Gly-Leu-Gln-Leu-Glu-Leu-Thr), representing amino acid sequence 180-188 ofthe 65-kD mycobacterial HSP, has been suggested to carry the critical epitope(s) for A A because of its ability to stimulate the arthritis-inducing T cell clone A2b as well as the arthritis-protective T cell clone A2c in vitro (Holoshitz, Matitiau & Cohen, 1984;Cohen et at., 1985;van Eden et al, 1988;, Based on these observations, it was suspected that immunization with the Correspondence: Dr X,-D, Yang, R-1056.…”
Section: Introductionmentioning
confidence: 99%